2012
DOI: 10.3109/01612840.2012.663064
|View full text |Cite
|
Sign up to set email alerts
|

Beginning the Recovery Journey in Acute Psychiatric Care: Using Concepts from Orem's Self-Care Deficit Nursing Theory

Abstract: A national agenda has been established for mental health systems to move toward a recovery model of care. Recovery principles are embedded in the foundations of nursing science and practice. Orem's Self-Care Deficit Nursing Theory (SCDNT) is in alignment with the ideals of recovery and can provide a structure for changing cultures on inpatient psychiatric units. SCDNT can guide research activities that link a patient's self-care abilities to improved recovery model outcomes. This paradigm shift is an opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Authors consider the competence of caregivers to be important for person-centred care, discussing the significance of leadership (10,17,23), adequate staffing (11,24), knowledge (15,19,(26)(27)(28)(29) and values (10,21). Authors discuss caregivers as using adapted forms of communication (25) and being culturally sensitive and competent (14,29,30).…”
Section: Attributesmentioning
confidence: 98%
See 1 more Smart Citation
“…Authors consider the competence of caregivers to be important for person-centred care, discussing the significance of leadership (10,17,23), adequate staffing (11,24), knowledge (15,19,(26)(27)(28)(29) and values (10,21). Authors discuss caregivers as using adapted forms of communication (25) and being culturally sensitive and competent (14,29,30).…”
Section: Attributesmentioning
confidence: 98%
“…In particular, authors stress the significance of competence, interprofessional collaboration and patient involvement. Several authors explicitly use person-centred care as relating to culture (9)(10)(11)(12)(13)(14)(15)(16)(17). Authors also talk about the context of care in terms of the structure, nature and function of a unit (18), setting (13), physical and psychosocial care environment (2), policies and procedures (11,19), therapeutic milieu (20,21) and systems and processes (22).…”
Section: Attributesmentioning
confidence: 98%
“…20,22 Other problems noted in these studies included highly variable and difficult-to-monitor nursing practices, 23 very limited individualized care planning, patient engagement, and shared decision making, all within the context of increasingly shorter stay and high-acuity settings that emphasize risk management and stabilization. 12,24 These challenges are exacerbated by the low morale observed on wards, with up to 40% of psychiatric nurses dissatisfied with their jobs 25 and, compared with community mental health workers, evidence of generally greater pessimism and less optimism about the potential for recovery of their clients.…”
Section: Problems and Barriers To Changementioning
confidence: 99%
“…Dashiff (1988) was the first to address the importance of self-care in psychiatric nursing, and a very limited numbers of research articles have focused on psychiatric nursing (Seed & Torkelson 2012). If persons with psychosis should have the opportunity to live a life like everyone else and be able to take the step from thought to action, the ability to self-care needs to be taken into consideration.…”
Section: Future Health Promotion Interventions Should Facilitate the mentioning
confidence: 99%
“…The self-care deficit nursing theory is oriented towards creating therapeutic, non-hierarchical relationships that are focusing upon recovery (Seed & Torkelson 2012). Research has shown that the ability to self-care has the potential to reduce re-hospitalisation and improve QoL (Cutler 2003).…”
Section: Future Health Promotion Interventions Should Facilitate the mentioning
confidence: 99%